Porous carbon, preparation method thereof and silicon-carbon material with high silicon content
Through the synergistic effect of modified nanosilicon dioxide and carbon nanotubes, porous carbon materials with high porosity and rich mesoporous structures are formed, which solves the problem of insufficient mesoporous content of existing pores of porous carbon materials and significantly improves the silicon carbon materials Battery performance.
Patent Information
- Application Number
- CN202411630772.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-14
AI Technical Summary
The interposer content of existing pores is insufficient and cannot effectively buffer the volume changes of silicon during charging and discharging, resulting in poor battery cycle stability and specific capacity.
By dispersing the modified nanosilicon dioxide and carbon nanotubes in carbon raw materials, spray granulation and pre-carbonization treatment, followed by removal of silica using hydrofluoric acid to form a rich and uniform mesoporous structure and pass through high temperature Activation and hydrofluoric acid treatment increase micropore pore size.
The deposition silicon content in silicon-carbon materials is significantly improved, the specific capacity and cycling stability of the battery are enhanced, and the stability and electron conductivity of the electrode structure are improved.
Smart Images

Figure CN119430142A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery negative electrodes, and in particular to porous carbon and a preparation method thereof, and a silicon-carbon material with a high silicon content. Background Art
[0002] Silicon-carbon materials combine the good conductivity and structural stability of carbon materials with the high lithium storage capacity of silicon, and are one of the ideal negative electrode materials for high-performance lithium-ion batteries. However, silicon undergoes significant volume expansion during the charge and discharge process, which not only causes the material to pulverize and reduce the cycle life of the battery, but also causes an increase in internal stress in the battery, affecting the safety performance of the battery.
[0003] Porous carbon plays an important role in the preparation of silicon-carbon materials. Its unique porous structure can provide an effective buffer space for the volume change of silicon during the charge and discharge process. This avoids excessive stress damage to the entire electrode structure, effectively maintains the stability of the electrode structure, and thus has a positive role in improving the cycle stability of silicon-carbon batteries. In addition, porous carbon can also improve the electronic conductivity and ion diffusion rate of silicon-carbon materials, which is beneficial to improving the overall performance of the battery.
[0004] At present, porous carbon is usually prepared by an activation reaction between coke and an alkaline activator under high temperature conditions. For example, the patent application with publication number CN109037679A discloses a petroleum coke-based porous carbon material and its preparation method and a silicon-carbon negative electrode material, which are prepared by mixing and calcining petroleum coke with a pore-forming agent such as potassium hydroxide. It has lower production costs and higher production efficiency.
[0005] Although the above method can form a porous structure to a certain extent, due to the limitations of the activation process, the porosity of the obtained porous carbon is relatively low, especially the formation of the internal pore structure is not as rich as the surface, and it is impossible to provide sufficient and uniform buffer space for the volume change of silicon during the charging and discharging process. In addition, the proportion of mesoporous (2-50nm) structure, which has a very outstanding effect on silicon deposition buffering, is obviously insufficient. The irrationality of this pore structure greatly limits the improvement of the gram capacity of silicon-carbon material batteries and the improvement of cycle stability. Summary of the invention
[0006] In order to solve the problem that the mesopore content in the current porous carbon structure is insufficient, which is not conducive to increasing the silicon deposition amount of the silicon-carbon material, resulting in poor battery discharge capacity and cycle stability, the present application provides a porous carbon and a preparation method thereof, and a silicon-carbon material with a high silicon content.
[0007] In a first aspect, the present application provides a method for preparing porous carbon, which comprises the following steps: Dispersing a carbon raw material, modified nano-silicon dioxide, and carbon nanotubes in a mass ratio of 1:0.1-0.3:0.001-0.1 in ethanol to obtain a mixed slurry, and drying the mixed slurry to obtain a carbon source precursor; In an inert atmosphere, the carbon source precursor is pre-carbonized and crushed to obtain a pre-carbonized powder, which is mixed with an alkaline activator and placed in an activation furnace for activation, washing, and drying to obtain an activated powder; The activated powder is added into a hydrofluoric acid solution and soaked to remove the modified nano-silicon dioxide, and the powder is filtered, washed and dried to obtain the product; The modified nano silicon dioxide is prepared by esterification reaction between fatty acid and nano silicon dioxide.
[0008] In any of the above technical solutions, the average particle size of the nano-silicon dioxide is 5 to 30 nm, and more preferably 10 to 20 nm.
[0009] Exemplarily, the average particle size of the nano-silica is 5 nm, 8 nm, 10 nm, 15 nm, 18 nm, 20 nm or 30 nm.
[0010] The above average particle size can be obtained by counting at least 200 typical samples using a scanning electron microscope, a light scattering instrument, a light scattering instrument, etc. Selecting nano-silica in the above particle size range can ensure that the particle size is mostly distributed in the range of 2 to 50 nm to form a sufficient amount of mesoporous structure.
[0011] In any of the above technical solutions, the carbon number of the fatty acid is 8 to 20. Preferably, the fatty acid is selected from one or more of caprylic acid, nonanoic acid, capric acid, lauric acid, myristic acid, palmitic acid and stearic acid.
[0012] In any of the above technical solutions, the preparation method of the modified nano-silica is: disperse the nano-silica in an organic solvent, add fatty acid and p-toluenesulfonic acid, carry out esterification reaction at a temperature of 110-130°C, centrifuge, wash and dry to obtain the modified nano-silica.
[0013] In any of the above technical solutions, the organic solvent is selected from toluene, dichloromethane or cyclohexane.
[0014] In any of the above technical solutions, the mass ratio of the nano-silicon dioxide, fatty acid and p-toluenesulfonic acid is 1:0.5-2:0.01-0.1.
[0015] In any of the above technical solutions, the carbon raw material is tar or resin.
[0016] Exemplarily, the tar is coal tar.
[0017] Exemplarily, the resin is a linear phenolic resin.
[0018] In the porous carbon preparation process of the present application, nano-silicon dioxide is added to the carbon raw material and spray granulation is carried out. After pre-carbonization, the obtained carbon particles are treated with hydrofluoric acid to remove the silicon dioxide in the carbon particle structure, thereby forming a rich and uniform mesoporous structure in the carbon particles, especially inside the carbon particles, providing sufficient space for silicon deposition and playing a good buffering role for the deposited silicon, thereby effectively improving the specific capacity and cycle stability of silicon-carbon material batteries.
[0019] In the preparation process of the porous carbon of the present application, high-temperature activation is first used to form pores to form a rich pore structure on the surface of the carbon particles, and then hydrofluoric acid treatment is performed. The hydrofluoric acid can not only penetrate into the interior to remove silicon dioxide, but also etch the surface pore structure to expand the pore size of micropores (less than 2nm), thereby increasing the number of mesopores.
[0020] In addition, nano-silicon dioxide has a large surface energy and is easy to agglomerate. For this reason, the present application uses fatty acids to modify the surface of nano-silicon dioxide to inhibit its agglomeration tendency. More importantly, the fatty acids grafted on the surface of nano-silicon dioxide are easy to pyrolyze and volatilize during the pre-carbonization process, which can increase the roughness of the inner wall of the resulting mesopores, especially when nano-silicon dioxide with a higher sphericity is used, which helps to increase the interface contact area between silicon and porous carbon after vapor deposition, improve the adhesion strength of silicon, reduce the shedding phenomenon caused by volume change, and help improve the cycle stability of the battery.
[0021] In any of the above technical solutions, the carbon nanotubes are single-walled and / or double-walled carbon nanotubes.
[0022] In any of the above technical solutions, the average particle size of the carbon source precursor is 10 to 50 μm.
[0023] In any of the above technical solutions, the solid content of the mixed slurry is 10-40%, more preferably 15-30%.
[0024] In any of the above technical solutions, the inert atmosphere is a nitrogen or argon atmosphere.
[0025] In any of the above technical solutions, the pre-carbonization temperature is 400-600°C.
[0026] In any of the above technical solutions, the pre-carbonization time is 1 to 5 hours.
[0027] In any of the above technical solutions, the activation treatment is to heat up to 280-450°C at a rate of 1-5°C / min and keep warm for 1-3h; then heat up to 700-900°C at a rate of 5-10°C / min and keep warm for 1-4h.
[0028] In any of the above technical solutions, the hydrofluoric acid solution has a concentration of 5 to 8 wt %.
[0029] In any of the above technical solutions, the mass ratio of the pre-carbonized powder to the alkaline activator is 1:1.5-3.8; the alkaline activator is selected from sodium hydroxide and / or potassium hydroxide.
[0030] In a second aspect, the present application provides a porous carbon prepared by any of the preparation methods described above.
[0031] In a third aspect, the present application provides a silicon-carbon material with a high silicon content, which is prepared by using the porous carbon prepared in any one of the above methods as a raw material and performing the following operations: The porous carbon is fed into a CVD deposition furnace, nitrogen is introduced and the temperature is raised to 600-800° C., and then silane gas is introduced to deposit silicon; then a carbon source gas is introduced to deposit carbon at 700-900° C. to obtain deposited porous carbon; The carbon raw material and the carbon nanotubes are dispersed in ethanol at a ratio of 100:0.5-1.5, mixed to obtain a coating slurry, sprayed on the surface of the deposited porous carbon, and carbonized at 700-900°C to obtain the coating slurry.
[0032] The silicon-carbon negative electrode material of the present application has porous carbon, nano-silicon deposited in the porous carbon pore structure, a first carbon layer covering the surface of the porous carbon, and a second carbon layer covering the first carbon layer. Among them, the first carbon layer is prepared by vapor deposition method, and has good density, which can reduce the direct contact between nano-silicon and electrolyte, and reduce the irreversible capacity loss caused by the volume change of silicon during charging and discharging. The second carbon layer contains carbon nanotubes, which have more outstanding strength and toughness, can absorb and disperse the volume change of silicon, and reduce the pulverization and electrical contact loss of silicon-carbon materials.
[0033] In any of the above technical solutions, the solid content of the coating slurry is 10-40%, more preferably 15-30%.
[0034] In any of the above technical solutions, the thickness of the carbon layer formed after the coating slurry is carbonized is 20 to 50 nm.
[0035] In any of the above technical solutions, the particle size of the silicon-carbon material is 5 to 10 μm.
[0036] In any of the above technical solutions, the silane gas is monosilane or disilane; the carbon source gas is selected from one or more of methane, ethane, propane, acetylene, ethylene, and propylene.
[0037] In any of the above technical solutions, the pressure during silicon deposition is 1 to 10 Torr.
[0038] In any of the above technical solutions, the pressure during carbon deposition is 10 to 100 Torr.
[0039] In any of the above technical solutions, the flow rate of silane gas is 10 to 100 sccm.
[0040] In any of the above technical solutions, the flow rate of the carbon source gas is 10 to 100 sccm.
[0041] In any of the above technical solutions, the silicon deposition time is 2 to 8 hours.
[0042] In any of the above technical solutions, the carbon deposition time is 1 to 5 hours.
[0043] In summary, this application has the following beneficial effects: The present application uses fatty acid-modified nano-silica as a pore-forming agent, and after carbonization, activation and hydrofluoric acid treatment, obtains porous carbon with high porosity and rich mesopore content, effectively increasing the deposited silicon content in the silicon-carbon material, and effectively improving the specific capacity and cycle stability of the battery. In addition, the silicon-carbon material of the present application has a first carbon layer obtained by deposition and a second carbon layer obtained by calcining a liquid carbon raw material, which excels in the ability to buffer silicon volume changes, and helps to further improve the cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is an electron microscope image of the porous carbon in Example 1-1 of the present application.
[0045] Figure 2 This is an electron microscope image of the silicon-carbon material in Example 2-1 of the present application.
[0046] Figure 3 It is the X-ray diffraction pattern of the silicon-carbon material in Example 2-1 of the present application. DETAILED DESCRIPTION Preparation Example
[0047] Preparation Example 1: A modified nano-silicon dioxide is prepared by the following operation: Disperse 10g of nano-silica (average particle size 10nm) in 500mL of toluene and disperse by ultrasonic to obtain a suspension; add 16g of lauric acid and 0.5g of p-toluenesulfonic acid to the suspension and stir evenly to obtain a mixed solution; transfer the mixed solution to a three-necked flask with a condenser and heat under reflux at 120℃ for 24h to perform an esterification reaction. After the reaction is completed, cool to room temperature, centrifuge to separate the nano-silica, wash with ethanol three times, and place the washed product in a vacuum drying oven and dry at 60℃ for 12 hours.
[0048] Preparation Example 2: A modified nano-silicon dioxide is prepared by the following operation: Disperse 10g of nano-silicon dioxide (average particle size 20nm) in 500mL of toluene and disperse by ultrasonic to obtain a suspension; add 20g of stearic acid and 0.8g of p-toluenesulfonic acid to the suspension and stir evenly to obtain a mixed solution; transfer the mixed solution to a three-necked flask with a condenser and heat under reflux at 130℃ for 24h to perform an esterification reaction. After the reaction is completed, cool to room temperature, centrifuge to separate the nano-silicon dioxide, wash with ethanol three times, and place the washed product in a vacuum drying oven and dry at 60℃ for 12 hours.
[0049] Preparation Example 3, a modified nano-silicon dioxide is prepared by the following operation: Disperse 10g of nano-silica (average particle size 15nm) in 500mL of toluene and disperse by ultrasonic to obtain a suspension; add 10g of decanoic acid and 0.3g of p-toluenesulfonic acid to the suspension and stir evenly to obtain a mixed solution; transfer the mixed solution to a three-necked flask with a condenser and heat under reflux at 120℃ for 24h to perform an esterification reaction. After the reaction is completed, cool to room temperature, centrifuge to separate the nano-silica, wash three times with ethanol, and place the washed product in a vacuum drying oven and dry at 60℃ for 12 hours.
[0050] Preparation Example 4, a modified nano-silicon dioxide is prepared by the following operation: Add 10g of nano-silica (average particle size 10nm), 10g of aminopropyltrimethoxysilane and 100mL of anhydrous ethanol into the reactor, stir and mix, heat to 60℃, stir and react for 1h. After the reaction is completed, release the material, remove the anhydrous ethanol on the upper layer after standing for a period of time, and then transfer the precipitate to a 110℃ oven and dry it for 2h. Example
[0051] Example 1-1, a porous carbon, is prepared according to the following steps: 100 g of resol phenolic resin (acid value 60 mgKOH / g), 17.5 g of modified nano-silica prepared in Preparation Example 1, and 0.5 g of single-walled carbon nanotubes (average diameter 1 nm) were weighed and dispersed in ethanol, and stirred to obtain a mixed slurry with a solid content of 35%. The mixed slurry was dried to obtain a carbon source precursor.
[0052] Under nitrogen atmosphere, the carbon source precursor is placed at 500°C for 3h pre-carbonization treatment, and airflow crushing is performed to obtain a pre-carbonized powder with an average particle size of 30μm. Take 100g of pre-carbonized powder and mix it with 290g of potassium hydroxide, send it into the activation furnace, and raise the temperature in the activation furnace to 350°C at a rate of 3°C / min, and keep it warm for 2h; then raise the temperature to 850°C at a rate of 6°C / min, and keep it warm for 2h. After the activation is completed, the material is cooled, washed with deionized water to neutrality, the residual alkali is removed, and dried in an oven to constant weight to obtain an activated powder.
[0053] The activated powder was soaked in a 7wt% hydrofluoric acid aqueous solution for 6 hours to remove the modified nano-silicon dioxide, the product was separated by centrifugation, the residual hydrofluoric acid and reactants were washed with deionized water, and dried at 170°C to control the moisture content at 6-9%. The activated carbon was then air flow crushed to control the median particle size at 8-9μm.
[0054] Example 1-2, a porous carbon, is prepared according to the following steps: 100 g of resol phenolic resin (acid value 100 mgKOH / g), 12 g of modified nano-silica prepared in Preparation Example 2, and 0.2 g of single-walled carbon nanotubes (average diameter 1 nm) were dispersed in ethanol and stirred to obtain a mixed slurry with a solid content of 20%. The mixed slurry was dried to obtain a carbon source precursor.
[0055] Under nitrogen atmosphere, the carbon source precursor is placed at 500°C for 3h pre-carbonization treatment, and airflow crushing is performed to obtain a pre-carbonized powder with an average particle size of 20μm. Take 100g of pre-carbonized powder and mix it with 350g of potassium hydroxide, send it into the activation furnace, raise the temperature in the activation furnace to 420°C at a rate of 5°C / min, and keep it warm for 2h; then raise the temperature to 800°C at a rate of 8°C / min, and keep it warm for 3h. After activation, the material is cooled, washed with deionized water to neutrality, remove residual alkali, and dried in an oven to constant weight to obtain activated powder.
[0056] The activated powder was soaked in a 5.5wt% hydrofluoric acid aqueous solution for 7 hours to remove the modified nano-silicon dioxide, and the product was separated by centrifugation. The residual hydrofluoric acid and reactants were washed with deionized water, and dried at 170°C to control the moisture content to 6-9%. The activated carbon was then air-blasted to control the median particle size to 6-7μm.
[0057] Example 1-3, a porous carbon, is prepared according to the following steps: 100 g of resol phenolic resin (acid value 60 mgKOH / g), 26 g of modified nano-silica prepared in Preparation Example 3, and 0.8 g of double-walled carbon nanotubes (average diameter 1.5 nm) were weighed and dispersed in ethanol, and stirred to obtain a mixed slurry with a solid content of 30%. The mixed slurry was dried to obtain a carbon source precursor.
[0058] In a nitrogen atmosphere, the carbon source precursor is placed at 600°C for 3 hours of pre-carbonization treatment, and airflow crushing is performed to obtain a pre-carbonized powder with an average particle size of 40μm. Take 100g of pre-carbonized powder and mix it with 175g of potassium hydroxide, send it into an activation furnace, and raise the temperature in the activation furnace to 300°C at a rate of 3°C / min, and keep it warm for 2 hours; then raise the temperature to 900°C at a rate of 10°C / min, and keep it warm for 1 hour. After the activation is completed, the material is cooled, washed with deionized water to neutrality, the residual alkali is removed, and dried in an oven to constant weight to obtain an activated powder.
[0059] The activated powder was soaked in an 8wt% hydrofluoric acid aqueous solution for 6 hours to remove the modified nano-silicon dioxide, the product was separated by centrifugation, the residual hydrofluoric acid and reactants were washed with deionized water, and dried at 170°C to control the moisture content at 6-9%. The activated carbon was then air-blasted to control the median particle size at 8-9μm.
[0060] Comparative Example 1-1 is a porous carbon, which is different from Example 1-1 in that the modified nano-silica in Preparation Example 1 is replaced by an equal amount of the modified nano-silica in Preparation Example 4.
[0061] Comparative Example 1-2, a porous carbon, is different from Example 1-1 in that the preparation steps are as follows: 100 g of resol phenolic resin (acid value 60 mgKOH / g) and 0.5 g of single-walled carbon nanotubes (average diameter 1 nm) were weighed and dispersed in ethanol, and stirred to obtain a mixed slurry with a solid content of 35%. The mixed slurry was dried to obtain a carbon source precursor.
[0062] In a nitrogen atmosphere, the carbon source precursor is placed at 500°C for 3 hours of pre-carbonization treatment, and airflow crushing is performed to obtain a pre-carbonized powder with an average particle size of 30μm. Take 100g of pre-carbonized powder and mix it with 290g of potassium hydroxide, send it into the activation furnace, and raise the temperature in the activation furnace to 350°C at a rate of 3°C / min, and keep it warm for 2 hours; then raise the temperature to 850°C at a rate of 6°C / min, and keep it warm for 2 hours. After the activation is completed, the material is cooled, washed with deionized water to neutrality, the residual alkali is removed, and dried at 170°C, and the moisture content is controlled at 6-9%. Then the activated carbon is airflow crushed to control the median particle size to 8-9μm.
[0063] Example 2-1, a silicon-carbon material with a high silicon content, is prepared according to the following steps: The porous carbon of Example 1-1 is sent into a CVD deposition furnace, nitrogen is introduced, the air in the furnace is exhausted as much as possible, the temperature is raised to 650°C, monosilane gas is introduced at a flow rate of 30sccm, and silicon deposition is performed at a pressure of 3Torr; acetylene gas is introduced after deposition for 6 hours, and the acetylene gas flow rate is 60sccm. Carbon deposition is performed at a temperature of 800°C and a pressure of 40Torr for 3 hours to obtain deposited porous carbon.
[0064] Weigh 100g of resol phenolic resin (acid value 60mgKOH / g) and 1g of carbon nanotubes, disperse them in ethanol, stir and mix to obtain a coating slurry with a solid content of 30%, spray the coating slurry on the surface of the deposited porous carbon, carbonize at 800℃ for 3h to form a carbon layer with a thickness of 30nm, and obtain a carbon silicon material with a high silicon content.
[0065] Example 2-2, a silicon-carbon material with a high silicon content, is prepared according to the following steps: The porous carbon of Example 1-2 is sent into a CVD deposition furnace, nitrogen is introduced, the air in the furnace is exhausted as much as possible, the temperature is raised to 750°C, monosilane gas is introduced at a flow rate of 50sccm, and silicon deposition is performed at a pressure of 5Torr; acetylene gas is introduced for 4 hours of deposition, and the acetylene gas flow rate is 20sccm. Carbon deposition is performed at a temperature of 850°C and a pressure of 60Torr for 2 hours to obtain deposited porous carbon.
[0066] Weigh 100g of resol phenolic resin (acid value 60mgKOH / g) and 0.8g of carbon nanotubes and disperse them in ethanol. Stir and mix to obtain a coating slurry with a solid content of 30%. Spray the coating slurry on the surface of the deposited porous carbon and carbonize it at 750°C for 3h to form a carbon layer with a thickness of 40nm to obtain a carbon silicon material with a high silicon content.
[0067] Example 2-3, a silicon-carbon material with a high silicon content, is prepared according to the following steps: The porous carbon of Example 1-3 is sent into a CVD deposition furnace, nitrogen is introduced, the air in the furnace is exhausted as much as possible, the temperature is raised to 750°C, monosilane gas is introduced at a flow rate of 20sccm, and silicon deposition is performed at a pressure of 10Torr; acetylene gas is introduced after deposition for 5 hours, and the acetylene gas flow rate is 50sccm. Carbon deposition is performed at a temperature of 800°C and a pressure of 50Torr for 3 hours to obtain deposited porous carbon.
[0068] Weigh 100g of resol phenolic resin (acid value 60mgKOH / g) and 1.5g of carbon nanotubes, disperse them in ethanol, stir and mix to obtain a coating slurry with a solid content of 20%, spray the coating slurry on the surface of the deposited porous carbon, carbonize at 900℃ for 2h to form a carbon layer with a thickness of 20nm, and obtain a carbon silicon material with a high silicon content.
[0069] Example 2-4, a silicon-carbon material with a high silicon content, is prepared according to the following steps: The porous carbon of Example 1-1 is sent into a CVD deposition furnace, nitrogen is introduced, the air in the furnace is exhausted as much as possible, the temperature is raised to 650°C, monosilane gas is introduced at a flow rate of 30sccm, and silicon deposition is performed at a pressure of 3Torr; acetylene gas is introduced after deposition for 6 hours, and the acetylene gas flow rate is 60sccm. Carbon deposition is performed at a temperature of 800°C and a pressure of 40Torr for 3 hours to obtain a carbon-silicon material with a high silicon content.
[0070] Example 2-5, a silicon-carbon material with a high silicon content, is prepared according to the following steps: The porous carbon of Example 1-1 was sent into a CVD deposition furnace, nitrogen was introduced, the air in the furnace was exhausted as much as possible, the temperature was raised to 650°C, monosilane gas was introduced at a flow rate of 30 sccm, silicon deposition was performed at a pressure of 3 Torr, and the deposited porous carbon was obtained by deposition for 6 hours.
[0071] Weigh 100g of resol phenolic resin (acid value 60mgKOH / g) and 1g of carbon nanotubes, disperse them in ethanol, stir and mix to obtain a coating slurry with a solid content of 30%, spray the coating slurry on the surface of the deposited porous carbon, carbonize at 800℃ for 3h to form a carbon layer with a thickness of 30nm, and obtain a carbon silicon material with a high silicon content.
[0072] Comparative Example 2-1, a silicon-carbon material with a high silicon content, differs from Example 2-4 in that the porous carbon of Example 1-1 is replaced with an equal amount of the porous carbon of Comparative Example 1-1.
[0073] Comparative Example 2-2, a silicon-carbon material with a high silicon content, differs from Example 2-4 in that the porous carbon of Example 1-1 is replaced by an equal amount of the porous carbon of Comparative Example 1-2. Performance testing
[0074] Experiment 1: Performance test of porous carbon structure Based on the nitrogen adsorption method, the pore size distribution of porous carbon is determined by measuring the adsorption and desorption curves using a specific surface area analyzer and a pore size analyzer. The specific surface area, total pore volume, mesopore (2-50 nm) pore volume and its proportion of porous carbon materials are calculated using the BET equation and the BJH method. The specific surface area of porous carbon is calculated using the BET equation, the total pore volume is calculated using the maximum adsorption amount of the adsorption isotherm, and the mesopore volume and its proportion are calculated using the BJH method.
[0075] Test 2: Silicon deposition content test of silicon-carbon material The content of Si element in the silicon-carbon negative electrode material was obtained by testing with an element analyzer.
[0076] Test 3: Electrical performance test Sample preparation: Using the silicon-carbon material prepared in Examples 2-1 to 2-5 and Comparative Examples 2-1 to 2-2 as the negative electrode active material, 91g of silicon-carbon negative electrode material, 4.05g of SP, 0.15g of SCNTs, 1.9g of CMC, 2.9g of SBR and 220mL of solvent were stirred and mixed to prepare a negative electrode slurry, which was coated on a copper foil, and the negative electrode sheet was obtained by drying, cold pressing and slitting; a metal lithium sheet was used as the counter electrode, 1M LiPF6-EC / DMC was used as the electrolyte, and a polypropylene film was used as the separator to assemble a button cell.
[0077] 1) Discharge capacity in grams: The assembled button cell was tested on a battery testing system with a test voltage range of 0.005V-1.5V. The cell was allowed to stand for 30 minutes, discharged at a constant current of 0.1C to 0.01V, allowed to stand for 5 minutes, and then discharged at a constant current of 0.02C to 0.005V. The discharge capacity in grams was divided by the mass of the active substance (silicon-carbon material) to obtain the discharge capacity in grams of the silicon-carbon material.
[0078] 2) Initial charge and discharge capacity: Use a battery tester (RSS1400) to perform the first charge and discharge, charge to 4.2V, then discharge to 3.0V, and record the initial discharge capacity.
[0079] 3) Cycle stability test: Set up a battery tester (RSS1400) for cycle testing, usually using constant current charge and discharge mode. Charge to 4.2V at 0.1C, then discharge to 3.0V at 0.1C, cycle 300 times, record the discharge capacity, and calculate the discharge capacity retention rate after 300 cycles.
[0080] Table 1. Test results of porous carbon pore structure performance
[0081] Table 2. Test results of electrical properties of silicon-carbon materials
[0082] Analysis of test results: Combining Example 1-1 and Comparative Example 1-2 with Table 1 and Table 2, it can be seen that the present application uses nano-silicon dioxide as a pore-forming agent, and cooperates with the hydrofluoric acid treatment process to effectively increase the proportion of mesoporous structures in porous carbon, thereby increasing the deposited silicon content. This is reflected in the performance of silicon-carbon materials (corresponding to Example 2-1 and Comparative Example 2-2), and their discharge capacity and cycle stability (300 cycle capacity retention rate) are improved.
[0083] Combining Example 1-1 and Comparative Example 1-1 and Table 1 and Table 2, it can be seen that compared with the modification with silane coupling agent, the carbon silicon material (corresponding to Example 2-1 and Comparative Example 2-1) obtained by modifying nano-titanium dioxide with fatty acid has a more outstanding surface in terms of cycle performance. The reason may be that the grafted modified fatty acid is easy to pyrolyze and volatilize during the carbonization and calcination process, thereby increasing the roughness of the inner wall of the pores, improving the interface bonding strength between the deposited silicon and the porous carbon, and improving the cycle stability. However, the silicon-oxygen-silicon chain segment formed by the grafting modification with silane coupling agent has high stability, and it is difficult to achieve the same effect.
[0084] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A method for preparing porous carbon, characterized in that: The following steps are included: Dispersing a carbon raw material, modified nano-silicon dioxide, and carbon nanotubes in a mass ratio of 1:0.1-0.3:0.001-0.1 in ethanol to obtain a mixed slurry, and drying the mixed slurry to obtain a carbon source precursor; In an inert atmosphere, the carbon source precursor is pre-carbonized and crushed to obtain a pre-carbonized powder, which is mixed with an alkaline activator and placed in an activation furnace for activation, washing, and drying to obtain an activated powder; The activated powder is added into a hydrofluoric acid solution and soaked to remove the modified nano-silicon dioxide, and the powder is filtered, washed and dried to obtain the product; The modified nano silicon dioxide is prepared by esterification reaction between fatty acid and nano silicon dioxide, and the average particle size of the nano silicon dioxide is 5-30nm.
2. The preparation method according to claim 1, characterized in that: The fatty acid has 8 to 20 carbon atoms.
3. The preparation method according to claim 1, characterized in that: The preparation method of the modified nano silicon dioxide is as follows: dispersing the nano silicon dioxide in an organic solvent, adding fatty acid and p-toluenesulfonic acid, carrying out esterification reaction at a temperature of 110-130° C., centrifuging, washing and drying to obtain the modified nano silicon dioxide.
4. The preparation method according to claim 1, characterized in that: The activation treatment comprises heating the temperature to 280-450° C. at a rate of 1-5° C. / min and keeping the temperature for 1-3 hours; then heating the temperature to 700-900° C. at a rate of 5-10° C. / min and keeping the temperature for 1-4 hours.
5. The preparation method according to claim 1, characterized in that: The concentration of the hydrofluoric acid solution is 5-8 wt %.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the pre-carbonized powder to the alkaline activator is 1:1.5-3.
8.
7. The preparation method according to claim 1, characterized in that: The alkaline activator is selected from sodium hydroxide and / or potassium hydroxide.
8. A porous carbon, characterized in that: The method is prepared according to any one of claims 1 to 8.
9. A silicon-carbon material with a high silicon content, characterized in that: The porous carbon prepared according to any one of claims 1 to 8 is used as a raw material and the following operations are performed to obtain the porous carbon: The porous carbon is fed into a CVD deposition furnace, nitrogen is introduced and the temperature is raised to 600-800°C, and silane gas is introduced to deposit silicon; Then, a carbon source gas is introduced to perform carbon deposition at 700-900° C. to obtain deposited porous carbon; The carbon raw material and the carbon nanotubes are dispersed in ethanol at a ratio of 100:0.5-1.5, mixed to obtain a coating slurry, sprayed on the surface of the deposited porous carbon, and carbonized at 700-900°C to obtain the coating slurry.
10. The preparation method according to claim 9, characterized in that: The silane gas is monosilane or disilane; the carbon source gas is selected from one or more of methane, ethane, propane, acetylene, ethylene and propylene.
Citation Information
Patent Citations
Petroleum coke-based porous carbon material, preparation method thereof and silicon-carbon negative electrode material
CN109037679A
Cited By
Preparation method of uniformly coated silicon-carbon negative electrode material
CN120809808A
Carbonization-activation continuous fluidized bed system and process method
CN121929697A